Lasers and ancillary treatments for scar management: personal experience over two decades and contextual review of the literature. Part I: Burn scars - Rory B McGoldrick; Adam Sawyer; Christopher R Davis; Evgenia Theodorakopoulou; Maxwell Murison (SAGE Publishing, 2016)
The formation of a wide range of excessive scars following various skin injuries is a natural consequence of healing. Scars resulting from surgery or trauma affect approximately 100 million people per annum in the developed world and can have profound physical, aesthetic, psychological and social consequences. Thus, scar treatment is a priority for the plastic surgeon. We aim to explore new approaches to the management of such scarring. The senior authors current use of laser technology, chemotherapeutic agents, pharmacotherapy and cryosurgery will be reviewed. This is placed in the context of the current literature and evidence base and is illustrated with case studies, starting with burns scars in part I, and focusing on keloid and hypertrophic scars in part II, acne scars in part III and finally pigmented scars in part IV. In Part I we focus on burns scar treatment with fractional ablative 10,600 nm wavelength carbon dioxide (CO2) laser therapy.